Students’ Difficulties and Strategies on Translation Process at English Education Department - Farida Repelita Waty Kembaren; Maryati Salmiah; Putri Intan Ramadani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This research investigated to know the students difficulties and strategies on translating religious story from English into Indonesian in English Department. The research method used in conducting this research is descriptive qualitative. This is intended so that readers can find out what errors often occur when students translate. This study found that there were three difficulties in the translation results of students. Namely social culture difficulties, religious cultures difficulties, and material culture difficulties. After anlyzing the results of the students translation the researcher can see several factors causing mistakes made by students such as most students make some words into the target language (addition words), students lack of words choice and most students during translatio process mistranslated of the word (omission), In addition, students also lack understanding of context and their lack of understanding of words related to cultural aspects. To overcome these difficulties in the translation process, there are only 3 strategies that are most widely used by the participants in the translation process. The three strategies are as follows: translation by more general, translation by paraphrase using related words and translation by more natural words. It was easy to understand the content of the text when they used these three translation strategies.